2020
DOI: 10.1002/est2.211
|View full text |Cite
|
Sign up to set email alerts
|

Techno‐economic analysis of a stand‐alone photovoltaic system with three different storage systems for feeding isolated houses in south Algeria

Abstract: This paper presents a technical and economic simulation of a solar photovoltaic system with three different storage types. Battery lead‐acid, battery lithium‐ion, and hydrogen storage have been used to cover the consumption of houses in an isolated village in southwest Algeria. The main objective of this study is trying to use the roof of the houses to cover consumption by installing solar panels and build a room for electric equipment like inverter, battery, power system management, and so forth. The proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…The techno-economic analysis of solar PV system with LA, Li-Ion, and hydrogen storage to supply the demand of isolated village is discussed in another work. 21 The analysis reported reveals that the hydrogen storage is the one that provides due to low excess energy with no unmet load. The study identifies the major challenges of battery energy storage system application with battery charging and discharging strategy along with battery connection, efficiency of conversion, and battery lifetime.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The techno-economic analysis of solar PV system with LA, Li-Ion, and hydrogen storage to supply the demand of isolated village is discussed in another work. 21 The analysis reported reveals that the hydrogen storage is the one that provides due to low excess energy with no unmet load. The study identifies the major challenges of battery energy storage system application with battery charging and discharging strategy along with battery connection, efficiency of conversion, and battery lifetime.…”
Section: Introductionmentioning
confidence: 98%
“…The techno‐economic analysis of solar PV system with LA, Li‐Ion, and hydrogen storage to supply the demand of isolated village is discussed in another work 21 . The analysis reported reveals that the hydrogen storage is the one that provides due to low excess energy with no unmet load.…”
Section: Introductionmentioning
confidence: 99%
“…Invented by Gaston Planté in 1859, the lead‐acid battery (LaB) (the maximum open‐circuit voltage for a cell is 2.041 V) is still the most usually used globally due to its low cost, easy manufacturing, and good recyclability 1 . Battery cycling is the most critical aspect of its operation in a photovoltaic system 2 . During the daily cycle, the battery is charged all day and discharged by the night‐time load 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they suggested that combining hydrogen technology components instead of a battery component is feasible. Ammari et al 45 compared three different storage types, which were utilized to supply energy for the basic household needs in an isolated village in Algeria. The three storage types were lead‐acid, lithium‐ion batteries, and hydrogen storage.…”
Section: Introductionmentioning
confidence: 99%